Supporting workers with disabilities: a scoping review of the role of human resource management in contemporary organisations. (17th May 2016) - Cavanagh, Jillian; Bartram, Timothy; Meacham, Hannah; Bigby, Christine; Oakman, Jodi; Fossey, Ellie
Abstract : This is a scoping review of literature on human resource management (HRM) and management practice that impacts on workers with physical, mental health and intellectual disabilities, employed or entering paid employment. The aim is to illuminate the use of HRM practices, managerial attitudes and employee outcomes in the disability literature. The methodological research framework commenced with seven databases and was supported with evidenced‐based literature to find three main themes. Themes highlight the management and employer support for workers with disabilities, discrimination and attitudes towards employment of this cohort of workers, and performance and employment outcomes. As governments around the world seek to reduce welfare costs and increase the employment of people with disabilities this paper is timely. Overall, the paper contributes to a dearth of literature on the management of people with disabilities at the workplace to unpack the key barriers, challenges and trends, and develop a comprehensive research agenda. Key points: This paper presents a scoping review of human resource management (HRM) and disability literature to inform management practice and research on workers with disability. The paper identifies literature on physical, mental health and intellectual disability. The scoping review identifies management and employer knowledge and support, discrimination and attitudes towards the employment of workers with disabilities, and their performance and employment outcomes.